Editorial dossier “Orality and criminal procedure guarantees”: what orality can we speak? - Flaviane de Magalhães Barros (Revista Brasileira de Direito Processual Penal, 2017)
This editorial develops an analysis of the understanding of orality from the fundamental guarantees. The orality is a technique that allows the amplification of the full defense and adversary proceedings. The editorial proposes a critical dialogue with the conformation of orality in the theory of the Brazilian process and its strong connection with the inquisitorial tradition. The debate with the authors of the dossier allows us to discuss other possibilities for understanding orality and experiences in Chilean and Argentine procedural reforms.